LIVING QUR’AN: TRADISI WIRID AL-MA’TSŪRĀT DI SMAIT ABU BAKAR BOARDING SCHOOL KULON PROGO - Fatah, Abdul Fatah (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2020)
This article discusses about the Living Quran study of recitation of wirid al-Ma?ts?r?t at Abu Bakar Senior Boarding School Kulon Progo. It focuses on the practice of wirid al-Ma?ts?r?t which is read routine by students at the school. This phenomenon, which has been going on since the school was founded, has positive values for students. They feel the positive impact of the tradition of reciting it in accordance with the function of the Koran as al-dzikr (to remembrance of Allah) and al-syif?? (to treat for illness). With the Living Quran method, which is presented by descriptive-analitically method the result is indicate that interaction with the Koran in the form of recitation can provide peace of mind for the reader, whether recited individually or in congregation.